The relationship between work environments, leadership styles and employee performance mediating role of job satisfaction - Alkaabi, Maktoum Rashed (2023)
In the United Arab Emirates (UAE) educational system, it is consequently critical to determine the implications of the workplace environment and styles of leadership on employee performance. Employees in UAE public organizations encounter some challenges, including a lack of workplaces for them to conduct their jobs properly, noise that causes irritation relying on the duty they are assigned, and the atmosphere wherein they operate. Therefore, the study aims to identify the effects of the factors on employee job performance, investigate the relationship between work environment, leadership styles, and employee job performance in UAE. The study also aims to propose a new model for work environment and leadership style on job performance using quantitative approach. A non-probability sampling more specific, purposive sampling was adopted in this study. A total of 368 questionnaires were distributed through monkey survey to five schools. Thus, an aggregate of 283 completed questionnaires was obtained. Taking after the gathering of data from employees in public schools, more specifically and the questionnaires will be checked at the Emirates National School in the United Arab Emirates to ensure the data's elimination, finality, and uniformity. Not everyone in the survey answers all of the questions. Responses may well have been ignored entirely because the participant did not understand the question, did not realize the response, was unwilling to complete or was just unconcerned with the need to reply to the entire survey. The analysis of Moment Structures (AMOS) in Structural Equation Modelling (SEM) was used to analyze the data. The result showed a significant relationship between employee job performance and work environment with a P-value .042. Meanwhile, the relationship between employee job performance and leadership style was found to be significant, with a P-value .031. The relationship of work environment, leadership style and employee job performance were also significant and found to be mediated by employee job satisfaction with a P-value. 006. Then, the relationship between work environment and job satisfaction was also significant with a p-value .016. Finally, the relationship of leadership style, employee job performance and job satisfaction were also significant with a P-value .037. The outcome of this study showed that in order to improve the performance of employee job performance in UAE, the developed model in this study could be used and will benefit the UAE government agencies. Likewise, a leadership style which encourages fellow employees to take on challenging projects will push employees to give it their all since they believe that the leader is assisting in their professional development. Last but not least, this study contributes to the development of a model which will help to improve risk operational management in enhancing the work environment and leadership style on job performance in UAE. Also, this research is to guide policymakers to It improves and opens up a new arena of employee’s performance research and helps to improve professional knowledge and helped the academics to understand the nature of aspects distressing employee performance in general, particularly in the context of the UAE.